Enganando a audiência e a consciência em um jogo de espelhos : a fragmentação da estética contemporaníssima de Santiago Nazarian em Feriado de Mim Mesmo - Cabral, Rayssa Duarte Marques (2015)
This dissertation has as study object the book Feriado de mim mesmo (2005), by the contemporary Brazilian writer Santiago Nazarian. Considering the recent production, this paper aims to contribute to the formation of the author’s academic literary criticism, and also to reflect on contemporary literature and “the most contemporary” literature, the newcomers writers of 90s and Zero Zero generations and their process of canonization; to treat the extreme individualization, to what we call “umbiguismo solipsista”, making a reflection on the romance genre and its protagonists increasingly introspective. The critical analysis of the work took some apparatus of psychoanalysis, by the use of concepts such as “mirror stage”, “aware”, “unconscious” and “small other” and “big other”, to fill gaps and clarify certain left in the narrative. Therefore, we opted for the presentation of the analysis through detailed presentation of the plot that was linearly recounted and, when appropriate, interrupted by this researcher.